Epilithic Algal Diversity of Cimil Stream (Rize, Turkey) - Beyhan Taş; Özlem Yılmaz (Turkish Journal of Agriculture: Food Science and Technology)
The Ikizdere Valley is one of priority ecologic region within 200 areas where is under protection in the world. It is natural conservation area. In this study, epilithic algal diversity of Cimil Stream in the Cimil (Tiron) Valley where is one of the most important protection areas were investigated. The ecological structure of the stream is to determine by using indicator algae. According to sampling results obtained from four different stations after rainy and dry seasons (November 2010 and August 2011), total 113 taxa belongs to five different division were identified. Diatoms have the most species diversity in terms of other groups (74, 65%). This was followed by Cyanophyta (28, 25%), Charophyta (6, 5%), Chlorophyta (4, 4%) and Euglenophyta (1, 1%). Achnanthidium minutissimum, Cocconeis pediculus, C. placentula, Cymbella affinis, Gomphonema parvulum, G. truncatum, Encyonema minutum, Hannaea arcus, Navicula menisculus, N. salinarum ve Nitzschia palea are common and dominant diatom species in the Cimil Stream. Indicator species showed that the ecological situation of the Cimil Stream is not yet under intense pressure pollution. However, it is seen that the stream showed a change towards β-α-mesosaprobic conditions from oligosaprobic top to bottom. For the area's tourism potential is very high, it is recommended that the necessary measures take as to maintaining ecological structure in future.